2021
DOI: 10.1128/spectrum.01653-21
|View full text |Cite
|
Sign up to set email alerts
|

Reverted HIV-1 Mutants in CD4 + T-Cells Reveal Critical Residues in the Polar Region of Viral Envelope Glycoprotein

Abstract: Our previous mutagenesis study revealed that serine at position 534 of HIV-1 Env is critical for viral infectivity. We found that HIV-1 Env containing serine to proline mutation at position 534 (S534P) are incapable of supporting virus-cell and cell-cell fusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The disulfide loop is at the site of non-covalent contact with C5 in gp120 and forms part of the furin recognition site where gp120-gp41 are cleaved ( Cao et al, 1993 ; Caffrey, 2001 ; Sen et al, 2007 ; Yi et al, 2016 ). It is therefore possible that S534A and T536A could negatively affect the association of gp120-gp41 during viral entry and suggests a shift to a cell-to-cell route of infection in the presence of these mutations ( Freed et al, 1990 ; Lu et al, 2019 , 2021 ; Hikichi et al, 2021 ). Hikichi et al (2021) showed that where viral entry is inhibited, the virus reverts to a predominant cell-to-cell mode of infection ( Hikichi et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The disulfide loop is at the site of non-covalent contact with C5 in gp120 and forms part of the furin recognition site where gp120-gp41 are cleaved ( Cao et al, 1993 ; Caffrey, 2001 ; Sen et al, 2007 ; Yi et al, 2016 ). It is therefore possible that S534A and T536A could negatively affect the association of gp120-gp41 during viral entry and suggests a shift to a cell-to-cell route of infection in the presence of these mutations ( Freed et al, 1990 ; Lu et al, 2019 , 2021 ; Hikichi et al, 2021 ). Hikichi et al (2021) showed that where viral entry is inhibited, the virus reverts to a predominant cell-to-cell mode of infection ( Hikichi et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In gp41, key mutations that were positively selected in PI-treated isolates were seen in the FPPR (S534A and T536A), which is an important region involved in the association of gp120 with gp41 during viral fusion (Freed et al, 1990;Cao et al, 1993). Lu et al (2021) showed that S534 formed hydrogen bonds with N656 in HR2 and suggested that this interaction stabilized the formation of the Env trimer, and was crucial for viral fusion (Markosyan et al, 2003;Lu et al, 2019Lu et al, , 2021. While we did not see any interaction between S534 and N656 in the wildtype isolates, possibly because this study was limited to the interactions seen in the monomer structures, the mutant S534A formed a hydrogen bond with L602, found in the disulfide loop that connects HR1 and The Ectodomain structure showing a salt bridge between residues K601 and E654 in the WT, and PCSK75 showing a salt bridge between D632 and R585.…”
Section: Discussionmentioning
confidence: 99%